2009
DOI: 10.1590/s0100-204x2009001100010
|View full text |Cite
|
Sign up to set email alerts
|

Inoculantes formulados com polímeros e bactérias endofíticas para a cultura da cana-de-açúcar

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da utilização, em campo, de inoculantes compostos pela mistura de estirpes de bactérias diazotróficas e pelos polímeros carboximetilcelulose e amido, sobre a fixação de nitrogênio, em cana-de-açucar. O delineamento experimental foi de blocos ao acaso, em esquema fatorial 4x2, com quatro formas de fornecimento de N: controle absoluto, controle nitrogênio (adubação com 120 kg ha -1 de N), inoculante polimérico líquido (IPC 0,8), e inoculante polimérico gel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
0
17
0
15
Order By: Relevance
“…In the first ratoon crop, inoculation caused a significant increase in dry matter production compared to the absolute control, but did not differ from the N-fertilized control. In the second ratoon crop, variety RB867515 showed no response to inoculation, but was responsive to N fertilization in stalk yield, dry matter and total N. The lack of response of this variety (RB867515) to treatments with inoculation and N fertilization in the plant-cane crop may be characteristic of the variety, since it produces high yields on N-poor soils (Silva et al, 2009;Schultz et al, 2012). In the first ratoon crop, due to the reduction in available soil N after the plant-cane harvest, there was no response in the variety to the treatments with inoculation and N fertilization in the accumulation of total dry matter production, which was however not reflected in significant increases in stalk yield and in total N, stocks, probably due to the high use efficiency of available soil N of this variety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first ratoon crop, inoculation caused a significant increase in dry matter production compared to the absolute control, but did not differ from the N-fertilized control. In the second ratoon crop, variety RB867515 showed no response to inoculation, but was responsive to N fertilization in stalk yield, dry matter and total N. The lack of response of this variety (RB867515) to treatments with inoculation and N fertilization in the plant-cane crop may be characteristic of the variety, since it produces high yields on N-poor soils (Silva et al, 2009;Schultz et al, 2012). In the first ratoon crop, due to the reduction in available soil N after the plant-cane harvest, there was no response in the variety to the treatments with inoculation and N fertilization in the accumulation of total dry matter production, which was however not reflected in significant increases in stalk yield and in total N, stocks, probably due to the high use efficiency of available soil N of this variety.…”
Section: Resultsmentioning
confidence: 99%
“…Govindarajan et al (2006) evaluated the inoculation of Burkholderia vietnamiensis, strain MG43, in the varieties Co 86032 and Co 86027 of micropropagated sugarcane after different evaluation periods up to 12 months after planting, and found that inoculation with strain MG43 promoted increases of 20 and 19 % in dry matter production of Co 86032 and Co 86027, respectively. Testing the same inoculum as in this study in a medium texture Hapludult, Silva et al (2009) found that stalk yield increased by 50 Mg ha -1 in variety RB72454 and 30 Mg ha -1 in variety RB867515, 11 months after planting, compared to the absolute control; these increases were similar to those recorded in the control fertilized with 120 kg ha -1 N. Similar results to those mentioned above were reported by Schultz et al (2012) in studies carried out for two years in a Fluventic Eutrudept in the region of Campos dos Goytacazes, Rio de Janeiro, for variety RB867515. The results obtained to date and reported in the literature show that diazotrophic inoculation in sugarcane increased the crop yield potential, but with great variability in the responses and influence of soilclimatic factors involved in the production process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bactérias diazotróficas utilizadas na fixação de nitrogênio em gramíneas (ROESCH et al, 2005;MENDONÇA et al, 2006;GUI-MARÃES et al, 2007;MATTOS et al, 2008, SILVA et al, 2009) e outras espécies (WEBER et al, 2000;BAL-DOTTO et al, 2010) têm sido estudadas nos últimos anos. Estes estudos mostram a efetividade deste tipo de associação ao hospedeiro.…”
Section: Introductionunclassified
“…Bactérias diazotróficas podem associar-se à cana-deaçúcar, naturalmente, ou ser inoculadas para promover efeitos benéficos (Silva et al, 2009). Algumas espécies de bactérias endofiticas capazes de fixar N atmosférico como Gluconacetobacter diazotrophicus, Herbaspirillum spp., Azospirillum amazonense, Burkholderia spp.…”
Section: Introductionunclassified